Prognostické faktory karcinomu děložního hrdla - Mouková, L; Nenutil, R; Fabian, P; Chovanec, J (Klinicka onkologie, 2013)
Standardized gynecological oncological therapeutical guidelines are based on ordinary predictive factors, such as depth of stromal invasion, histopathological type of tumor, lymphovascular space invasion, lymph node metastases. Unfortunately, the power of these prognostic factors is not able to determine the safety of this procedure in the relation to disease recurrence in a group of patients who are indicated for conservative operations. This is the appropriate area for new, especially biomolecular prognostic factors (proteins: p63, TAp63, p16, p21, p27, COX-2, genes: hTERC, MYCC). Moreover, comprehensive evaluation of cervical cancer prognostic factors and assessment of new biomarkers of cancer can ease prediction of risk of spread outside primary localization and determine probability of disease recurrence. This information can help to individualize surgical, radiotherapeutic and chemotherapeutic treatment.
Keywords: Uterine Cervical Neoplasms; ženské pohlaví; nádorové biomarkery; prognóza; Humans; Female; nádory děložního čípku; Prognosis; lidé; Biomarkers, Tumor